2005
DOI: 10.1002/hep.20518
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of hepatitis C virus in patients successfully treated for chronic hepatitis C

Abstract: It is unclear whether the current antiviral treatment for chronic hepatitis C virus (HCV) infection results in complete elimination of the virus, or whether small quantities of virus persist. Our study group comprised 17 patients with chronic HCV who had sustained virological response (SVR) after interferon/ribavirin treatment. Serum and peripheral blood mononuclear cells were collected 2 to 3 times at 3-to 6-month intervals starting 40 to 109 months (mean, 64.2 ؎ 18.5 months) after the end of therapy. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
317
7
10

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 290 publications
(359 citation statements)
references
References 48 publications
23
317
7
10
Order By: Relevance
“…These results contrast with those from studies that reported the detection of HCV RNA in the PBMC of spontaneously resolved and treatment-induced aviremic subjects. [20][21][22] These authors speculated that persistent HCV RNA in PBMC may reflect the presence of a long-lived HCV reservoir [20][21][22] (reviewed by Feld and Liang 19 ). The difference with our results may be due to the more stringent definition of plasma aviremia used here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results contrast with those from studies that reported the detection of HCV RNA in the PBMC of spontaneously resolved and treatment-induced aviremic subjects. [20][21][22] These authors speculated that persistent HCV RNA in PBMC may reflect the presence of a long-lived HCV reservoir [20][21][22] (reviewed by Feld and Liang 19 ). The difference with our results may be due to the more stringent definition of plasma aviremia used here.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,36 The PBMC tested here were purified directly from blood without external stimulation. It therefore remains formally possible that nonspecific PBMC stimulation could have increased residual PBMCassociated HCV RNA to detectable levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of HEPATOLOGY, Radkowski et al 7 confirm and expand upon the important finding of HCV persistence. Using similar methods to those employed by Pham's group, they looked for the presence of HCV RNA in serum and PBMCs from patients who were persistently HCV RNA negative by conventional assays after spontaneous or treatment-induced recovery.…”
Section: H Epatitis C Virus (Hcv) Infects Between 170 Andmentioning
confidence: 76%
“…Of those, only 2 (1.2% of all sustained responders) had a serological relapse up to 3.5 years later. 19 It is likely that using the sensitive techniques of Radkowski et al, 7 HCV RNA would have been detected in a significant proportion of these cohorts; the implication being that despite low-level viral persistence, clinical improvement is still the most common outcome. Whether the presence, quantity, and location of replicating virus has any impact on clinical outcome remains to be seen.…”
Section: H Epatitis C Virus (Hcv) Infects Between 170 Andmentioning
confidence: 99%